Myokines and Heart Failure: Challenging Role in Adverse Cardiac Remodeling, Myopathy, and Clinical Outcomes - Berezin, A. E.; Berezin, A. A.; Lichtenauer, M.; Березін, Олександр Євгенійович (Hindawi, 2021)
Heart failure (HF) is a global medical problem that characterizes poor prognosis and high economic burden for the health system and family of the HF patients. Although modern treatment approaches have significantly decreased a risk of the occurrence of HF among patients having predominant coronary artery disease, hypertension, and myocarditis, the mortality of known HF continues to be unacceptably high. One of the most important symptoms of HF that negatively influences tolerance to physical exercise, wellbeing, social adaptation, and quality of life is deep fatigue due to HF-related myopathy. Myopathy in HF is associated with weakness of the skeletal muscles, loss of myofibers, and the development of fibrosis due to microvascular inflammation, metabolic disorders, and mitochondrial dysfunction. The pivotal role in the regulation of myocardial and skeletal muscle rejuvenation, attenuation of muscle metabolic homeostasis, and protection against ischemia injury and apoptosis belongs to myokines. Myokines are defined as a wide spectrum of active molecules that are directly synthesized and released by both cardiac and skeletal muscle myocytes and regulate energy homeostasis in autocrine/paracrine manner. In addition, myokines have a large spectrum of pleiotropic capabilities that are involved in the pathogenesis of HF including cardiac remodeling, muscle atrophy, and cardiac cachexia. The aim of the narrative review is to summarize the knowledge with respect to the role of myokines in adverse cardiac remodeling, myopathy, and clinical outcomes among HF patients. Some myokines, such as myostatin, irisin, brain-derived neurotrophic factor, interleukin-15, fibroblast growth factor-21, and growth differential factor-11, being engaged in the regulation of the pathogenesis of HF-related myopathy, can be detected in peripheral blood, and the evaluation of their circulating levels can provide new insights to the course of HF and stratify patients at higher risk of poor outcomes prior to sarcopenic stage.